Peran Edukasi dan Sosialisasi Komisi Pemilihan Umum Jakarta Utara dalam Meningkatkan Kesadaran Pemilih Baru melalui Program Pendidikan Pemilih di SMA/SMK - Natasya Puspa Adelia Nurak; Komang Adi Sastra Wijaya (YASIN, 2026)
Elections are the primary instrument for implementing democracy and require public participation and political awareness, particularly among first-time voters, while low levels of political literacy in this group remain a challenge to realizing high-quality elections. This study aimed to analyze the role of education and outreach conducted by the North Jakarta General Elections Commission (KPU Jakarta Utara) in enhancing the awareness of new voters through voter education programs at the senior and vocational high school (SMA/SMK) level. A descriptive qualitative method was employed, with data collected through in-depth interviews, non-participant observation, and documentation. The findings show that the voter education programs organized by KPU Jakarta Utara contributed to increasing students’ understanding of democratic values, voters’ rights and obligations, and the importance of participation in elections. The delivery of material in an interactive and contextual manner encouraged active participant engagement and helped foster a critical attitude toward electoral information. Although constraints were found, such as the influence of information circulating on social media and the varying characteristics of participants, the program was considered fairly effective in building the political awareness of first-time voters. These findings underscore that voter education in schools is a strategic effort to shape voters who are aware, critical, and responsible in the electoral democratic process.